Recent Advances in the Fabrication and Functionalization of Nanostructured Carbon Spheres for Energy Storage Applications - Kiet Le Anh Cao; Ferry Iskandar; Eishi Tanabe; Takashi Ogi (KONA Powder and Particle Journal, 2022)
The development of energy storage devices providing high energy and power densities and long-term stability will play an important role in the future utilization of sustainable energy sources. Numerous efforts have been devoted to achieving these requirements, especially the design of advanced electrode materials. For this reason, there is growing interest in the innovation of new carbon-based materials with enhanced electrochemical performance. Nanostructured carbon spheres (CSs) have attracted significant attention due to their prominent properties, such as high surface area, excellent electrical conductivity, tunable porosity, and surface functionality. This review offers a comprehensive overview into the recent advances of nanostructured CSs within the last five years, focusing on synthetic strategies for producing carbon particles with precisely controlled morphologies and interior structures, as well as the potential applications of these particles as high-performance electrode materials in rechargeable batteries and supercapacitors. The challenges and perspectives on future research directions are highlighted, focusing on the controlled synthesis and functionalization of nanostructured CSs with tunable structures and properties that are well-suited to practical applications. This review is intended to serve as a helpful resource to researchers involved in the fabrication of new CS materials and the development of methods to control their structure and morphology.